(3HMhK GdUMGaI (B/s - (3YHO GdMejO, eMeOs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 1997)
(3jGJj gPG GdcJGH GSJceGdG ddNWhW GdYGeI GdJj GSJgOaJ WQM GJLGgGJ GdHMK h GOhGJg HeG jJab eY GdfeGPL GdYdejI aj eLGd GdGJUGd GdLeGgjQj (B- (3GdGYdGe (B- (3HUaI YGeI haQhY GdeYQaI hjSGjQ GjVG GdGJLGgGJ GdadSajI h GdfXQjI h GdJWHjbjI GdeYGUQI ddGSJaGOI efgG aj JMOjO GWQ GdHMK GdYdej GdeNJdaI aj gPg GdeLGdGJ s
Keywords: (3GdEYdGes; (3GdUMGaIs; (3efgLjI GdHMK GdYdejs